Finding Galictis cuja (Molina, 1782) (Carnivora, Mustelidae) at a northern Chilean site in the potential distribution area of the species - Pablo Valladares-Faúndez; Francesco Canepa; Constanza Rubilar Ordoñez; Nicole Álvarez-Henríquez (Check List)
According to current literature, Galictis cuja (Molina, 1782) does not inhabit the desert of Chile. However, a previous ecological niche analysis had indicated a high probability of the mustelid Quique’s occurrence in the ravines that cross the northern desert of Chile. We present the ﬁrst ﬁnding of Galictis cuja in the northern desert of Tarapaca region, Chile, apparently attacked and killed by dogs, which indicates an expansion of its distribution range and the utilization of microhabitats.